Al-Minhajul-muhasaby lil Amaliyat Al-Murabahal fil-Masharif Al-Islamy - JALF, Ahmad Muhammad ad Muhammad (Al-Ma'had Al-Alamy, Kairo, 1996)
Al-Minhajul-muhasaby lil amaliyat al-murabahal fil-masharif al-Islamy